Some initial findings on the behaviour and design of mine-shaft steelwork and conveyances - G. J. Kringe (The Southern African Institute of Mining and Metallurgy, 1986)
The results of a series of measurements of accelerations and guide-roller loads made on mineshaft conveyances are given, together with the predictions of these accelerations and loads based on a computer programme. The analysis of the measurements is described, and the results of the measurements and computer predictions when compared show reasonable agreement. Some parameters that increase the guide-roller loads are identified, and their effects are studied, together with some comments on the total loads. Finally, a possible format for a design specification is discussed, and some tentative design values are given.